Actively Minimize Rocket Roll-Rate During the Coast Phase - Purdy, Ellyssa Marie (Proceedings of the Wisconsin Space Conference, 2023)
In the 2021-2022 Collegiate Rocket Competition, participating teams were tasked with the development and implementation of an active roll-control system onboard their rocket. To reduce the rotation of an object, the principal of conservation of momentum was applied by adjusting the angular momentum of a mass inside the object. This principle was implemented in the Phantastic Phoenom’s 2022 rocket to minimize the roll-rate during the coast phase of flight. The components utilized to accomplish this include a three-inch steel tube, Raven4 altimeter, six-axis accelerometer, Arduino Nano microcontroller, and a stepper motor. The mass housed inside the rocket was reduced by 40% to achieve the weight needed to reach the predicted apogee. Despite several unforeseen challenges the day of the competition launch, the rocket completed a successful launch. The Phantastic Phoenoms are proud to be able to win third place in this competition.